Sleep quality, behaviour, disorders prevalence and chronotype in elite junior and senior athletes - Pullinger, S. A.; Adhikari, R.; Bawari, B.; Pérez Armendáriz, M. L.; Manathanath, A.; Bommasamudram, T.; Edwards, B. J. (Biological Rhythm Research, 2025)
The aims were to compare quality(PSQI)/behaviour(ASBQ)/disorder(ASSQ) of sleep and chronotype(MEQ) in i)male/female Indian Tier 3-5 classified athletes, ii)adults/adolescents, iii)across different sports, iv)with/without injury. Indian athletes in athletics(n=36), boxing(n=72), judo(n=35) and wrestling(n=59) competing in national/international competitions took part (92 female/110 male) completed four questionnaires. Mean±SD:age:18.3±3.0yrs, mass:63.0±10.0kg, stature:168.0±8.8cm. 59% reported poor PSQI (global score 6.5±2.9), with sleep duration (7.1±0.9h), poor ASBQ (43.1±6.7) and mild sleep disorder (ASSQ-SDS:5.3±2.3). Chronotype was mainly intermediate (53%), with 43% moderate morning-types. 64% of Athletics athletes reported good sleep quality, compared to the other sports (range 29-40%,P=0.01). We found a positive correlation (r=0.524,P<0.001) for sleep quality against sleep screening score but none for sleep disorder/chronotype. The correlation did not change when adjusted by factors such as sex/injury presence/sport played. Results suggest 59% report poor sleep quality, 14.9% moderate-severe sleep difficulties. 26.8% were recommended to be assessed for sleep disorder. Sex/sport/injury/age/chronotype do not contribute to poorer sleep quality.